Do affective cues validate behavioural metrics for search? - McDuff, Daniel; Thomas, Paul; Rowan, Kael; Craswell, Nick; Czerwinski, Mary (SIGIR 2021, 2021)
Traces of searcher behaviour, such as query reformulation or clicks, are commonly used to evaluate a running search engine. The underlying expectation is that these behaviours are proxies for something more important, such as relevance, utility, or satisfaction. Affective computing technology gives us the tools to help confirm some of these expectations, by examining visceral expressive responses during search sessions. However, work to date has only studied small populations in laboratory settings and with a limited number of contrived search tasks. In this study, we analysed longitudinal, in-situ, search behaviours of 152 information workers, over the course of several weeks while simultaneously tracking their facial expressions. Results from over 20,000 search sessions and 45,000 queries allow us to observe that indeed affective expressions are consistent with, and complementary to, existing "click-based" metrics. On a query-level, searches that result in a short dwell time are associated with a decrease in smiles (expressions of "happiness") and that if a query is reformulated the results of the reformulation are associated with an increase in smiling—suggesting a positive outcome as people converge on the information they need. On a session-level, sessions that feature reformulations are more commonly associated with fewer smiles and more furrowed brows (expressions of "anger/frustration"). Similarly, sessions with short-dwell clicks are also associated with fewer smiles. These data provide an insight into visceral aspects of search experience and present a new dimension for evaluating engine performance.